Pharmacological abortion - Chazan, Bogdan (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
Definitions of abortion typically omit the child, although induced pregnancy termination is meant to deprive it of life. The chapter defines abortion as the deliberate killing of a child before birth, distinguishing medical and surgical methods; the medical method uses agents causing the child's death and inducing contractions that expel the body.In second-trimester eugenic abortion the child may be born alive. First-trimester medical abortion is becoming the most common method of prenatal homicide worldwide, though not permitted in Poland even on eugenic grounds. Contrary to popular belief, it is more dangerous to the mother than surgical abortion, causing complications including haemorrhage and infertility; risks rise further at home without supervision.Medical abortion, increasingly performed worldwide including in Poland, causes numerous child deaths and endangers maternal health; these risks warrant wider publicity.